A PROSPECTIVE COMPARATIVE STUDY OF FUNCTIONAL OUTCOME IN PATIENTS TREATED WITH INTERLOCKING NAILING AND DYNAMIC COMPRESSION PLATING FOR FRACTURE SHAFT OF HUMERUS IN ADULTS - HARSH LAPSIWALA,; SHANDILYA, ANURODH; RATHORE, BHANU PRATAP; SHAH, PRACHI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The purpose of this study is to compare the functional outcome between patients who underwent intramedullary interlocking nailing treatment and those who had Dynamic Compression plating applied to the fractured shaft of the humerus. Methods: A prospective comparative study involving 30 people who had humeral shaft fractures was carried out. Fractures treated at the Department of Orthopaedics, Pacific Medical College and Hospital, Udaipur, between December 2020 and November 2022 using intramedullary interlocking nailing and Dynamic Compression plating. Results: According to our analysis, there is no appreciable difference in the fracture union times between the two techniques. The incidence of infection was greater in the plating group than in the patients who received closure reduction and an interlocking nail procedure. Conclusion: The interlocking nail group in our study reported higher complications. The majority of them involved excruciatingly poor shoulder function. However, both treatment techniques’ secondary complications a group of interlocking nails were more common than they should have been. I, therefore, come to the conclusion that patients can be treated with dynamic compression plating and interlocking nailing for a fractured humerus shaft. Intramedullary interlocking nailing is a safe and effective alternative therapy of diaphyseal fractures in the humerus. It can be used by those who have osteoporosis segmentation-and polytrauma-affected fractures.